Fraternity and Terror: The Organization of Violence in Everyday Life - METCALFE, ANDREW (Mankind, 1984)
This paper was inspired by participant observation in the Coalfields towns of the Hunter Valley in New South Wales. It is an attempt to demonstrate the significance of violence in the political practice of coal‐miners. This significance has been overlooked in the recent enthusiasm for studies of ‘dominant ideologies’. Beyond this, the paper is an attempt to theorize the role of routine violence in the formation, maintenance and dissolution of social groups. The processes of group formation are an important subject for any theory of political practice.